The Risks and Benefits of School Integration for Participating Students: Evidence from a Randomized Desegregation Program - Peter Bergman (Institute of Labor Economics (IZA), 2018)
This paper studies the impact of a lottery-based desegregation program that allows minority students to transfer to seven school districts serving higher-income, predominantly-white families. While prior research has studied the impacts of such a program receiving students, this paper studies the effects on participating students. In the short run, students who receive an offer to transfer are more likely to be classified as requiring special education and their test scores increase in several subjects. In the medium run, college enrollment increases by 8 percentage points for these students. This is due to greater attendance at two-year colleges. There is no overall effect on the likelihood of voting. However, the offer to transfer significantly increases the likelihood of arrest. This is driven primarily by increases in arrests for non-violent offenses. Almost all of these effects - both the risks and the benefits - stem from impacts on male students. Male students have higher test scores, college enrollment rates, and are significantly more likely to vote, but they also experience nearly all of the effects on arrests.
Keywords: I20; I21; I24; I28; 330; desegregation; education; inequality